The effects of a 3-day mountain bike cycling race on the autonomic nervous system (ANS) and heart rate variability in amateur cyclists: a prospective quantitative research design - Anton Swart; Demitri Constantinou (BMC, 2023)
Abstract Background The acute and chronic adaptation of endurance athletes' hearts shows that increased volume of endurance exercise might cause an acute reduction in cardiac function, causing a physiological cascade that leads to the release of cardiac biomarkers specific to cardiomyocyte stress. Heart rate variability (HRV) is a valuable tool used as a physiological measurement to evaluate the autonomic nervous system (ANS). It is frequently used to assess cardiac autonomic regulation, determining a patient's risk for unfavorable events. This study set out to determine the changes in the ANS by participating in a 3-day mountain bike cycling race in amateur cyclists using HRV as an outcome measure. Methods Sixteen healthy participants (male and female) participating in a 3-day mountain bike cycling race underwent five-minute resting electrocardiography recordings in a supine position 2 days before the race (baseline testing). In addition, HRV measurements were recorded after each race day and 24 h post-race (recovery). Results Time-domain and frequency-domain measures showed significant changes from baseline HRV parameters after each race day (p ≤ 0.05). In addition, our data revealed that the mean heart rate and R-R variability intervals did not return to baseline values after 24 h of recovery. Thus, autonomic nervous system (ANS) alterations may be due to changes in cardiac sympatho-vagal balance. Conclusions The main strength of this study is using HRV as a measuring and screening tool to assess cardiac autonomic activity, whereby the state of the ANS before and after endurance races can be measured. Thus, physicians, athletes, and coaches can determine the stress of endurance races on the ANS and plan recovery strategies. The reasoning is that if the ANS is in a state of sub-optimal function, susceptible amateur athletes might be at risk for a cardiovascular event or maladaptation due to the endurance race.